Influence of lipopolysaccharide on graft versus host reactivity of lipopolysaccharide-unresponsive C3H/HeJ mice. - Rampy, P A (1979)
It was initially reported that lipopolysaccharide (LPS)-unresponsive C3H/HeJ mice are refractory to LPS at the B-lymphocyte level, but more recently it has been shown that other cells are similarly unaffected. The current study was undertaken to study an in vivo LPS-modulated disease process involving macrophage-T cell interactions. Adult CBA/J and C3H/HeJ mice were used as spleen donors, and graft versus host reactions were induced in BALB/c neonates. Prior LPS treatment of CBA/J adults decreased the ability of their spleen cells to cause fatal graft versus host disease in BALB/c neonates, whereas no difference was found between injection of spleen cells from normal or LPS-treated C3H/HeJ mice. Similar results were obtained with these cell types when the mouse spleen mixed leukocyte culture system was used. In a carbon clearance assay for stimulation of the reticuloendothelial system with LPS, it was found that the rate of phagocytosis was significantly increased in BALB/c and CBA/J mice 72 h after inoculation of LPS. No stimulation was seen in rate of carbon uptake in the C3H/HeJ animals after treatment with phenol-extracted LPS or with butanol-extracted LPS. An LPS-induced protective serum factor was produced only in the LPS-responsive CBA/J mice and was specific for the syngeneic cells.